Nafamostat mesylate augments survival in rats afflicted by exertional heat stroke - Qingwei Lin; Zhuqing Luo; Longping He; Lincui Zhong; Qingbo Zeng; Ye Zhou; Qi Chen; Xingping Deng; Xiaomin Song; Qing Song; Qing Song; Jingchun Song; et al. (Frontiers in Pharmacology)
ObjectiveTo evaluate the impact of Nafamostat mesylate (NM) in improving survival outcomes among rats subjected to exertional heat stroke.MethodsThis study involved a cohort of 45 specific pathogen-free (SPF) male Sprague Dawley (SD) rats. After successfully inducing exertional heat stroke, the rats were randomly divided into three groups: the Control group (Con, n = 15), the Exertional Heat Stroke group (EHS, n = 15), and the Nafamostat Mesylate group (NM, n = 15). A subset of ten rats from each group was selected for a 72-h survival analysis. Three hours following the successful establishment of the model, blood samples were collected under anesthesia for comprehensive analysis. This included routine hematological tests, coagulation assessments, and quantitative proteomics analysis, which were later validated using Parallel Reaction Monitoring (PRM). Additionally, tissue samples were harvested from the brain, heart, lung, kidney, liver, and duodenum of rats in each group for subsequent pathological examination.ResultsThe 72-h survival rate in the NM group was markedly higher than that observed in the EHS group. Pathological assessments indicated a notable reduction in thrombus formation within the brain, lungs, and liver in the NM group when compared to the EHS group. Furthermore, the NM group exhibited an elevated platelet count and a significant reduction in prothrombin time (PT) and activated partial thromboplastin time (APTT) relative to the EHS group. Proteomic profiling identified a total of 1,971 differentially expressed proteins, with 160 proteins being downregulated and 52 upregulated in the NM group as compared to the EHS group. PRM validation confirmed that the NM group significantly dampened the expression levels of key differential proteins, including ribosomal protein P2 (rpLP2), Histone 4c16 (H4c16), neutrophilic granule protein (NGP), and inositol monophosphatase 1 (Impa1), which are implicated in anti-inflammatory responses, suppression of immune-mediated thrombosis, and enhancement of cellular metabolism.ConclusionNM mitigates coagulopathy, alleviates thrombus burden, and improves the 72-h survival rate in EHS rats through the modulation of differentially expressed proteins, specifically rpLP2, H4c16, NGP, and Impa1.